The Influence of Learning Model and IQ on Knowledge of A Balanced Nutrition Healthy Eating - Kecuk Tri Prasetya; Junaidi Junaidi; Ika Novitaria Marani (Gladi : Jurnal Ilmu Keolahragaan, 2023)
This study aims to determine the effect of learning models and IQ on knowledge of a healthy balanced nutritious diet. Used an experimental research method with a treatment design by level 2x2. The results of study (1) there is a difference in the increase in knowledge of students who are given a jigsaw type cooperative learning model and guided inquiry learning model based on the value of F(OA) = 50.109 and p-value = 0,000 < 0,05. (2) There is an interaction between the learning model (factor A) and IQ (factor B) towards increasing knowledge of a healthy, nutritious and balanced diet based on the value of F(OAB) = 18.12 and p-value = 0,000 < 0,05. (3) there are differences in the knowledge of students who have a high IQ with a balanced, healthy, nutritious diet using the jigsaw cooperative learning model and the guided inquiry learning model. Based on Qhitung = 3,10 > Qtabel (0,05;4:30) = 2,89. (4) there is no difference in the knowledge of students who have a low IQ with the cooperative learning type of jigsaw and guided inquiry learning models based on the value of Qcount = 0.47 < Qtabel (0,05;4:30) = 2,89